Research Trends in the Use of Games in Early Childhood Education: A Bibliometric Study - Ulkhatiata, Id’ha Tutfi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Games are a part of the learning media that might surely attract a child’s interest, making the teaching and learning process more effective, efficient, and enjoyable. This study aims to present literature findings related to the use of games in early childhood education. The database was obtained using keywords such as ’game’ and ’child education,’ then stored in CSV format and analyzed using R-Bibliometrix (Biblioshiny) software. The included data type is journal articles. The study found that there was a fluctuation in the number of publications, with the highest production peak in 2022, totaling 192 articles. The authors who have contributed the most articles on the use of games in this field are Krustrup P and Larsen MN. The majority of scholarly works were still dominated by institutions from North America, particularly the United States, with the participation of 87 countries. The thematic map indicated a connection between the themes of game usage located in the lower right quadrant, suggesting opportunities for further exploration.